Injections for weight loss: what’s new in GLP-1 RAs for obesity treatment – review - Zając, Małgorzata Maria; Zaucha, Radosław; Silldorff, Julia; Anczyk, Stanisław; Dudek, Marcin; Fura, Tomasz; Felińska, Zuzanna; Iszczuk, Oliwia; Gajkiewicz, Magdalena; Jaskółka, Magdalena (Quality in Sport, 2024)
Among the myriad challenges confronting contemporary medicine, the obesity epidemic stands out as one of the most critical, warranting special attention due to its association with numerous severe comorbidities and its significant consumption of both human lives and financial resource. This review presents recent clinical trials addressing the issue of the effects of Glucagon-Like Peptide 1 Receptor Agonists (GLP-1 RAs) in the management of overweight and obesity in non-diabetic patients and identifies areas requiring further investigation. GLP-1 RAs, initially used in the treatment of type II diabetes, represent some of the most promising pharmacotherapeutic agents for obesity. Their mechanism of action involves lowering glucose levels by stimulating insulin secretion, inhibiting glucagon secretion, and delaying gastric emptying. They also affect the centres of hunger and satiety, contributing to a reduction in food intake, including food cravings. In clinical studies, GLP-1 RAs have demonstrated effectiveness in reducing body weight in both diabetic and non-diabetic patients with fairly good tolerance. The discussion is grounded in three clinical studies that examine the use of liraglutide and semaglutide, and the development of a novel GLP-1 RA, ecnoglutide. The use of semaglutide and liraglutide is associated with significant weight reduction and a decrease in cardiovascular risk in non-diabetic patients, while ecnoglutide represents a promising new GLP-1 RA that requires further investigation.